Integrating Notion as a Structured Learning Media in Creative Projects and Entrepreneurship Courses: A Feasibility Study - Pramesti Dzikrina; Sita Nurmasitah (Universitas Negeri Semarang, 2026)
This study aims to develop and evaluate the feasibility of a Notion-based website as a structured learning medium for the Creative Projects and Entrepreneurship course in the Office Management program at SMK PGRI 1 Semarang. The study was motivated by the use of a manual, paper-based learning system and the distribution of learning materials through instant messaging applications, which were considered inefficient and poorly organized. This research employed a Research and Development (R&D) approach using the ADDIE model, limited to the development and feasibility evaluation stages of the product in the form of a Notion-based website. The feasibility of the developed media was assessed through validation by three media experts and three subject-matter experts using a four-point Likert scale questionnaire. The data were analyzed using descriptive percentage statistics to determine the feasibility level of the learning media. The results showed that the Notion-based website obtained a feasibility score of 94% from media experts and 90% from subject-matter experts, both categorized as highly feasible. These findings indicate that the Notion-based website is suitable for use as a structured learning medium that supports transparent attendance monitoring, project task management, and systematic delivery of learning materials in project-based learning at vocational high schools.